Paradigma Pendidikan Berbasis Ulul Albab dalam Perspektif Al-Quran dan Hadis - Nastiya Nurrohmatuz Zahroh; Nashlihah A’idah Manazilal Fitri; Risa Maela Hasanah (Prodi PAI STIT Raden Santri Gresik, 2025)
This article comprehensively discusses the concept of ulul albab from the perspective of the Qur'an and hadith and its relevance in the development of contemporary Islamic educational models. Ulul albab is a Qur'anic term that refers to a human being with a clear mind, a clean heart, and spiritual depth, so that he is able to grasp the wisdom of Allah's verses, both qauliyah and kauniyah. This study uses the library research method through the analysis of classical and contemporary Islamic texts related to ulul albab, the structure of human psychology, and its implementation in education. The discussion also explored the differences in the meaning of the four terms of the human mind, namely shadr, qalb, fu'ad, and lubb, as the conceptual foundation for the formation of the character of ulul albab. The results of the study show that ulul albab is not only an intellectual concept but also includes the integration of intellect, spirituality, morality, and professional maturity. UIN Maulana Malik Ibrahim Malang is one of the institutions that develops an educational paradigm based on ulul albab through the four pillars of KKKL (Spiritual Depth, Moral Majesty, Breadth of Knowledge, and Professional Maturity). This study concludes that the concept of ulul albab is relevant as a holistic model of Islamic character education to form a generation that is able to face the challenges of the times with wisdom, knowledge, and integrity.